Electric field and higher harmonics of RF plasma slit jet measured by antennas and VI probes - Polášková, Kateřina; Drexler, Petr; Klíma, Miloš; Macháč, Jan; Nečas, David; Švanda, Milan; Zajíčková, Lenka (IOP Publishing, 2024)
The cold atmospheric plasma jets change their character when interacting with the different surfaces. Since such interaction is the primary area of plasma jet applications, it is essential to monitor the process. The non-linearity of the RF plasma slit jet (PSJ) was analyzed using the VI probes and a novel method, the non-intrusive antenna measurements. Regardless of the experimental setup and gas mixture (Ar, Ar/O2, Ar/N2), the PSJ frequency spectrum consisted of the following main features: dominant fundamental frequency peak, relatively strong odd harmonics, and significantly weaker even harmonics. The lowest degree of non-linearity was recorded for the Ar PSJ ignited against a grounded target. Admixing a molecular gas increased the discharge non-linearity. It was attributed to the enhancement of secondary electron emission from the dielectric surfaces. In addition to the non-linearity analysis, the antenna spectra were for the first time used to determine the semi-quantitative values of the PSJ-radiated electric field. The electric fields decreased by a factor of 2 after the admixing of nitrogen and oxygen molecular gases. Out of the studied targets, the highest electric fields were observed when plasma impinged on the grounded targets, followed by the floating target (2x lower) and the PSJ ignited in the open space configuration (4x lower than in the grounded target configuration).

The cold atmospheric plasma jets change their character when interacting with the different surfaces. Since such interaction is the primary area of plasma jet applications, it is essential to monitor the process. The non-linearity of the RF plasma slit jet (PSJ) was analyzed using the VI probes and a novel method, the non-intrusive antenna measurements. Regardless of the experimental setup and gas mixture (Ar, Ar/O2, Ar/N2), the PSJ frequency spectrum consisted of the following main features: dominant fundamental frequency peak, relatively strong odd harmonics, and significantly weaker even harmonics. The lowest degree of non-linearity was recorded for the Ar PSJ ignited against a grounded target. Admixing a molecular gas increased the discharge non-linearity. It was attributed to the enhancement of secondary electron emission from the dielectric surfaces. In addition to the non-linearity analysis, the antenna spectra were for the first time used to determine the semi-quantitative values of the PSJ-radiated electric field. The electric fields decreased by a factor of 2 after the admixing of nitrogen and oxygen molecular gases. Out of the studied targets, the highest electric fields were observed when plasma impinged on the grounded targets, followed by the floating target (2x lower) and the PSJ ignited in the open space configuration (4x lower than in the grounded target configuration).
Electric field and higher harmonics of RF plasma slit jet measured by antennas and VI probes
Keywords: radio frequency plasma jet; atmospheric pressure; electrical parameters; electromagnetic field; higher harmonics; radio frequency plasma jet; atmospheric pressure; electrical parameters; electromagnetic field; higher harmonics